Enhancement of nitrite production via addition of hydroxylamine to partial denitrification (PD) biomass: Functional genes dynamics and enzymatic activities. (December 2020) - Zhang, Xingxing; Xia, Yunkang; Wang, Chaochao; Li, Jiajia; Wu, Peng; Ma, Liping; Wang, Yuguang; Wang, Yao; Da, Fanghua; Liu, Wenru; Xu, Lezhong
Graphical abstract: Highlights: Elevated 2.56-fold NO2 − -N accumulation of PD biomass in response to NH2 OH addition. High-level NH2 OH played transient inhibition roles on NO3 − -N reduction process. NH2 OH dosing exerted a slight promoting effect on EPS secretion and PN/PS ratios. Free NH2 OH affected functional genes and enzymes metabolism for denitrifiers. 15 20 mg/L NH2 OH was recommended to PD system with poor NO2 − -N performance. Abstract: This study investigated the activity of partial denitrification (PD) biomass/key enzymes, functional gene expressions in response to 0 50 mg/L hydroxylamine (NH2 OH) addition. Results indicated that NH2 OH contributed to nitrite (NO2 − -N) production, facilitating the maximum increase of nitrate (NO3 − -N) to NO2 − -N transformation ratio to 80.47 ± 2.82%, leading to 2.56-fold NO2 − -N higher than those of control. The observed transient inhibitory effect on NO3 − -N reduction process was attributed by high-level NH2 OH (35 50 mg/L). Enzymatic assays revealed the enhanced activity of both NO3 − -N and NO2 − -N reductase while the former showed obvious superiority which led to high NO2 − -N accumulation. These results were further confirmed by the corresponding functional genes ( nar G, nap A, nir S and nir K). Besides, negative influence of NH2 OH addition was limited to PD aggregates, due to the increasing secretion of extracellular polymeric substances (EPS) as well as proteins/polysaccharides ratios in tightly-bound structure of EPS.